1-(3-Phenylisoquinolin-1-yl)hydrazine - Manivel, P. (International Union of Crystallography, 2008)
The title compound, C(15)H(13)N(3), contains two independent molecules in the asymmetric unit. The isoquinoline moiety and phenyl rings form dihedral angles of 4.38 (2) and 10.14 (3)° in the two independent molecules. The crystal packing is stabilized by N—H⋯N molecular dimers formed across a center of symmetry.